Palladium(ii) and palladium(ii)–silver(i) complexes with N-heterocyclic carbene and zwitterionic thiolate mixed ligands: synthesis, structural characterization and catalytic properties. Issue 6 (23rd January 2017) - Wang, Yu-Ting; Gao, Bin-Bin; Wang, Fan; Liu, Shi-Yuan; Yu, Hong; Zhang, Wen-Hua; Lang, Jian-Ping
Abstract : A combination of Pd(ii ), an N-heterocyclic carbene (NHC), and a thiolate (Tab) yields several Pd–NHC–Tab complexes and an octanuclear Pd4 Ag4 –NHC–Tab cluster. Abstract : The integration of a geometrically rigid Pd(ii ), a coordinatively monotonous N-heterocyclic carbene 1, 3-dimethylimidazoline-2-ylidene (IMe), and a flexible zwitterionic thiolate 4-(trimethylammonio)benzenethiolate (Tab) affords a class of Pd–IMe–Tab complexes with various nuclearities, namely, trans -[Pd(IMe)2 (Tab)2 ](OTf)2 (2, mononuclear), cis -[Pd(IMe)2 (Tab)2 ](OTf)(Cl) (3a, mononuclear), cis -[Pd(IMe)2 (Tab)2 ](PF6 )2 ·MeCN (3b ·MeCN, mononuclear), [Pd2 (IMe)4 (Tab)2 ](PF6 )4 ·2MeCN (4 ·2MeCN, dinuclear) and [Pd4 (IMe)4 (Tab)6 ](OTf)6 (Cl)2 (5, tetranuclear). Further presence of Ag(i ) in the assembly provides a heterometallic octanuclear cluster of [Pd4 Ag4 (IMe)8 (Tab)10 ](PF6 )12 (6 ). Compounds2–6 are formed by the reaction of trans -Pd(IMe)2 Cl2 (1 ) with various additional reagents via different reaction pathways. These compounds are characterized by means of FT-IR, 1 H and 13 C NMR, ESI-MS, elemental analysis and X-ray crystallography. Notably, the skeleton of compound5 features a [Pd4 S4 ] parallelogram wherein each of the four Pd(ii ) centers bisects the edge defined by the S atoms. The main skeleton of compound6 is an oval-shaped Pd4 Ag4 S10 unit, featuring an edge-fused norbornane-like (Pd2 Ag4 S6 ) framework appended by two additional PdS2 motifs at the polar positions. Compounds5 and6 also feature Pd⋯Pd (5 ), Pd⋯Ag and Ag⋯Ag (6 ) interactions. Compound5 as a representative example is highly effective at catalyzing Suzuki–Miyaura couplings in water, highlighting the potential of applying these types of homo- and heterometallic clusters as catalysts for organic transformations in environmentally benign media.